Efficacy of Medical Expulsive Therapy in Renal Calculi Less than or Equal to 5 Millimetres in Size - Daga, Sudarshan; Wagaskar, Vinayak G; Tanwar, Harshawardhan; Shelke, Umesh; Patil, Bhushan; Patwardhan, Sujata (Urology Journal, 2016)
Purpose: Natural history and modality of treatment for asymptomatic renal calculi less than or equal to 5 millimetres in size is still unknown. Many options are available ranging from medical expulsive therapy to minimally invasive surgery. Till date no study has focussed on this very common but asymptomatic issue. Hence, this study is undertaken to evaluate efficacy of medical expulsive therapy in renal calculi less than or equal to 5mm in size. Materials and Methods: A prospective, parallel group, randomized study was carried out from 1st June 2014 to 31st May 2015, with total of 100 patients, 50 patients in each group. Patients with renal stones less than or equal to 5mm were included in the study. Group A Patients were administered medical expulsive therapy which included tamsulosin 0.4 mg daily at night time, furosemide 20mg, spironolactone 50mg in a single morning dose, and syrup potassium magnesium citrate 20Meq per dose three times a day for 12 weeks while group B patients were given placebo. The primary outcome variable was number of patients achieving clearance of stone during 12-week treatment period in both groups. Results: No statistically significant differences in age, gender, stone size, and calyceal stone location was found between the two treatment arms. A spontaneous stone expulsion rate of 50% (at 6 weeks) and 86 %( at 12 weeks) was noted in group A versus 28% (at 6 weeks) and 38 % (at 12 weeks) in group B. Less number of pain episodes and less analgesic medication was required in group A as compared to group B. Conclusion: Medical Expulsive therapy for 12 weeks significantly improves stone free rates in renal calyceal calculi less than or equal to 5mm.